Differential Transcriptomic Regulation in Sweet Orange Fruit (Citrus sinensis L. Osbeck) Following Dehydration and Rehydration Conditions Leading to Peel Damage - Romero, Paco; Lafuente, Maria Teresa; Alferez, Fernando (Frontiers in Plant Science, 2021)
Water stress is the most important environmental agent causing crop productivity and quality losses globally. In citrus, water stress is a main driver of fruit peel disorders that impact quality and marketability. An increasingly present postharvest peel disorder is non-chilling peel pitting (NCPP). NCPP is manifested as collapsed areas of flavedo randomly scattered on the fruit and its incidence increases due to abrupt increases in environmental relative humidity (RH) during postharvest fruit manipulation. In this work we have used a custom-made cDNA microarray containing 44k unigenes from Citrus sinensis (L. Osbeck) covering for the first time the whole genome from this species, to study transcriptomic responses of mature citrus fruit to water stress. We have compared global gene expression profiles of flavedo from Navelate oranges subjected to severe water stress with those of fruit subjected to rehydration stress provoked by changes in RH during postharvest, which enhances the development of NCPP. Our results show that NCPP is a complex physiological process that shares molecular responses with those from prolonged dehydration in fruit, but the damage associated to NCPP may be explained by unique features of rehydration stress at the molecular level, including membrane disorganization, cell wall modification, and proteolysis.